Numerical Study of the Effects of the Navier Slip Boundary Condition on the Hydrodynamic Performances of a Newtonian Fluid-lubricated Pad Bearing - Ihssane Messoude; Samir Aghzer (Journal of Applied and Computational Mechanics)
This study investigates the impact of the slip boundary condition at the Fluid/Solid interface on the hydrodynamic behavior of a pad bearing through a comprehensive numerical simulation. A modified Reynolds equation, derived from the Navier-Stokes equations and incorporating the Navier-type boundary conditions on the velocity field at wall contacts, was developed to model the system. The discretization of this equation was performed using the centered finite difference method where the resulting linear system of equations was numerically processed with the Gauss-Seidel iterative method enhanced by over-relaxation. The simulation reveals that introducing the slip condition allows the pad bearing to support loads even in configurations with divergent or parallel surfaces, a capability absent in conventional pad bearings. Specifically, for a convergence ratio of (1.5) and a slip zone covering (55%) of the upper surface, the pad bearing achieves a load capacity increase of (33.5%) compared to the conventional type. Furthermore, this non-conventional pad bearing reduces friction forces by up to (30%), enhancing performance while minimizing shear power dissipation. These numerical findings suggest that incorporating the slip boundary condition can significantly enhance both load capacity and efficiency in pad bearing applications.